2015
DOI: 10.1186/s12935-015-0184-2
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma polymorphisms and hepatitis B virus-related liver cirrhosis risk in a Chinese population

Abstract: BackgroundPrevious studies proved that interferon gamma (IFN-γ) gene polymorphisms were associated with the risk of hepatitis B virus (HBV) infection. However, the association between IFN-γ polymorphisms and HBV-related liver cirrhosis (HBV-LC) risk is still unclear.MethodsIFN-γ +874 T/A and +2109G/A genotypes were determined in 126 HBV-LC patients, 129 chronic hepatitis B(CHB) patients, and 173 early HBV infection controls using a sequence-specific primer-polymerase chain reaction and a polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…Therefore, the low IFNγ expression may reduce the host immune response to HBV, and these individuals are more prone to the infection. A study conducted by Sun and colleagues (2015) in a Chinese population revealed that IFN-γ +874T haplotype is potentially protective against persistent HBV infection [29]. Also in agreement with our results, in a rural area of Northern China IFN-γ+ 874 AA genotype showed to be associated with an increased risk of chronic HBV infection [30].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the low IFNγ expression may reduce the host immune response to HBV, and these individuals are more prone to the infection. A study conducted by Sun and colleagues (2015) in a Chinese population revealed that IFN-γ +874T haplotype is potentially protective against persistent HBV infection [29]. Also in agreement with our results, in a rural area of Northern China IFN-γ+ 874 AA genotype showed to be associated with an increased risk of chronic HBV infection [30].…”
Section: Discussionsupporting
confidence: 92%
“…Cytokines represent a substantial role in initiating and maintaining a suitable immune and inflammatory response of HBV infection through direct or indirect inhibition of viral replication (15,(41)(42)(43)(44)(45)(46). Therefore, several recent studies have paid attention to the effect of gene polymorphisms of cytokines on infectious disease outcome, response to vaccination and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of members of the CHB group were indicated by the following findings: elevated serum alanine aminotransferase (ALT) or aspartate aminotransferase (AST) levels (> 40 IU/mL); or HBV-DNA levels > 1,000 copies/mL. HBV-LC was diagnosed as described in our previous study [36]. The patient inclusions were primarily based on imaging examinations, through ultrasonography, magnetic resonance imaging, computed tomography, and pathological examination.…”
Section: Methodsmentioning
confidence: 99%